Societal disintegration in Northern Ireland - a 5-year update - Heskin, Ken (Economic & Social Studies, 1985)
The hypothesis that society in Northern Ireland is in imminent danger of collapse as a consequence of the prolonged conflict there is tested using trends in crime from 1960-1983 as an index of such an occurrence. Comparisons between trends in crime in Northern Ireland with those in the Republic of Ireland and England and Wales are made. In addition, trends in crime in the cities of Belfast and Dublin are compared. As in an earlier study employing the same method on crime data up to 1978, no evidence emerges to support the hypothesis and a remarkably close relationship between trends in crime in the three areas and two cities is observed.
Keywords: Crime - Northern Ireland; Crime - Ireland